Bipartite promoters and RNA editing of paramyxoviruses and filoviruses - le Mercier, Philippe (RNA, 2019)
A primary property of paramyxovirus bipartite promoters is to ensure that their RNA genomes are imprinted with a hexamer phase via their association with nucleoproteins, in part because this phase as well the editing sequence itself controls mRNA editing. The question then arises whether a similar mechanism operates for filoviruses that also contain bipartite promoters that are governed by the “rule of six,” even though these genomes need not, and given Ebola virus biology, cannot always be of hexamer genome length. This review suggests that this is possible and describes how it might operate, and that RNA editing may play a role in Ebola virus genome interconversion that helps the virus adapt to different host environments.